DIFFERENCES OF LEARNING OUTCOMES OF MICROCONTROLLER PRACTICES USING MICROCONTROLLER MCS51 TRAINING KIT - Edidas Edidas (Jurnal Teknologi Informasi dan Pendidikan, 2019)
This paper describes the differences in learning outcomes in the practice of Microcontroller System using MCS51 Microcontroller Trainer Kit. Trainer Kit The MCS51 microcontroller is tested to Electronics Engineering students who are studying in practice of Microcontroller System. The research method used is quasi experiment. The experimental class uses the MCS51 Microcontroller Trainer Kit as a medium of controlled learning medium using a self-assembled circuit on the Project Board. The results show that the learning outcomes of the exprient class is better than the control class